The Role of Impaired Mitochondrial Dynamics in MFN2-Mediated Pathology - Zaman, Mashiat; Shutt, Timothy E. (Frontiers in Cell and Developmental Biology, 2022)
The Mitofusin2 protein (MFN2), encoded by the MFN2 gene, was first described for its role in mediating mitochondrial fusion. However, MFN2 is now recognized to play additional roles in mitochondrial autophagy (mitophagy), mitochondrial motility, lipid transfer, and as a tether to other organelles including the endoplasmic reticulum (ER) and lipid droplets. The tethering role of MFN2 is an important mediator of mitochondrial-ER contact sites (MERCs), which themselves have many important functions that regulate mitochondria, including calcium homeostasis and lipid metabolism. Exemplifying the importance of MFN2, pathogenic variants in MFN2 are well-established to cause the peripheral neuropathy Charcot-Marie-Tooth Disease Subtype 2A (CMT2A). However, the mechanistic basis for disease is not clear. Moreover, additional pathogenic phenotypes such as lipomatosis, distal myopathy, optic atrophy, and hearing loss, can also sometimes be present in patients with CMT2A. Given these variable patient phenotypes, and the many cellular roles played by MFN2, the mechanistic underpinnings of the cellular impairments by which MFN2 dysfunction leads to disease are likely to be complex. Here, we will review what is known about the various functions of MFN2 that are impaired by pathogenic variants causing CMT2A, with a specific emphasis on the ties between MFN2 variants and MERCs.